Infusing Qur’anic moral codes into engineering studies: Selected themes - Shuriye, Abdi Omar (Serials Publications, 2006)
Engineering profession, like medical and other professions, has a deep impact on the society. It must, therefore, conform to the universally accepted engineering ethical values. Although medical ethics and some other professional ethics are quite developed for obvious reasons, in some form there exists engineering ethics also. It is a different thing that the compliance of engineering ethics rests on the political will of the state. When we comedown to individual scientists and technocrats, they have to comply with the ethical values to the possible extent. They have to abstain from doing some thing which in the long run might bring pain to the society rather than giving happiness to it. Sometimes, they know that what they are doing is not good to the society, yet they do that for their personal fame. This is unethical on their part. Likewise, they have to be objective and keep themselves free front all kinds of greed and influences. For instilling these values among the future scientists, it is not necessary to have a separate co-course on engineering ethics. It is the duty of all lecturers to emphasize on them from time to time. This will have a long-lasting impact on them. A vast majority of the literature on engineering ethics are based on western ethical principles. References on Islamic moral codes and engineering professionalism in particular, are virtually not emphasized. It is, therefore, a religious duty of all Muslim lecturers, especially in the institutions of higher education like the International Islamic university, to instill the Islamic engineering ethics among their pupils, so that they do not work for sheer frame or in detriment to the society. The paper is an attempt to this aspect and attempts to bring engineering education in line with injunctions of Qur'an and Sunnah ( prophetic traditions ).